PENERAPAN (BALANCE EXERCISE) TERHADAP RISIKO JATUH PADA LANSIA DI PANTI WERDHA PURI KEBAJIKAN KOTA BATAM : STUDI KASUS - Tavian, Aulia; Gemini, Savitri (Ensiklopedia of Journal, 2024)
Abstract: In Indonesia, the prevalence of elderly people with decreased muscle strength is 11.9% and 33% have muscle problems. The impact of decreased muscle strength in the lower extremities is that the feet cannot step firmly, standing is unstable because of balance problems which can lead to the risk of falling. The cause of the incident of falling due to balance disorders is 49.9% at the age of > 55 years and 67.1% at the age of > 65 years. This case study aims to provide Gerontic Nursing Care for the Elderly Against the Risk of Falling with the Application of Balance Exercise at the Puri Kebajikan Nursing Home in Batam City. The method used is a case study with the Times Up to Go Test (TUGT) measuring instrument, Berg Balance Scale (BBS), and Elderly Balance Assessment. The results of the assessment on Mrs. E are muscle strength on a scale of 3, has a history of falling, the use of a walker and the range of motion of the right extremity is limited. Nursing Problems of Physical Mobility Disorders and Risk of Falling. Nursing intervention and implementation were carried out for 7 days of balance exercise implementation, there was a decrease in the risk of falling in the Elderly Balance Assessment from a score of 10 (moderate risk of falling) to a score of 2 (low risk of falling), and in the BBS there was an increase from a score of 24 to a score of 40 and in the TUG from 49 seconds to 31 seconds and an increase in muscle strength from a scale of 3 to a scale of 4.Keywords: Risk of Falls, Gerontics, Balance Exercise